PENGARUH FASILITAS KERJA DAN KOMUNIKASI TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR PAGAR GUNUNG KABUPATEN LAHAT - Sukri Sukri (Jurnal Manajemen Bisnis Unbara, 2020)
Results of the discussion obtained value Y = 11.202 + 0.176 + 0.419. Constant value of 11.202 means that if the independent variables are ignored then the value of the Job Morval (Y) variable is 11.202. Value of Working Facilities (X1) variable is 0,176 which means if Working Facilities (X1) variable is increased 0,176 it will increase work spirit variable (Y) equal to 0,176. The value of the communication variable (X2) is 0.419 which means if the communication variable (X2) is increased by 0.419 then it will increase the work spirit variable (Y) by 0.419 The result of the coefficient value is 0.255 or 25%. This means that the independent variables have contribution to the dependent variable of 25% and the remaining 75% is influenced by other factors not examined by the writer. The results of the table above also explains the value of Adjusted R Square of 0.199 this means the independent variables have a relationship with the dependent variable of 0.199. The simultaneous test results obtained F calculated value of 4.609, with a significant level of 0.019 then obtained Sig value of 0.019, which means Sig 0.019 <0.05 then Ho is rejected and Ha accepted. This means that the Working Facilities (X1), and Communication (X2) variables influence the work spirit (Y) Testing the influence of work facility variables (X1) on the spirit of work (Y). The result of the above table with partial test is obtained value t_hitung for work facility variable (X1) obtained value of Sig = 0,371 which mean Sig 0,371> 0,05 meaning work facility variable (X1) have insignificant effect to variable (Y), hence Accepted and Ha rejected, so the hypothesis in this study is not proven to show there is significant influence of Working Facilities (X1) variable to the dependent variable Job Spirit (Y). Testing the influence of variables Communication (X2) to the Spirit of Work (Y). With the test partially obtained value t_hitung for communication variables (X2) obtained value Sig = 0.045 which means Sig 0.045 <0.05 which means the communication variable (X2) has a significant effect on the variable Spirit Work (Y), then Ho is rejected and Ha accepted, So the hypothesis in this study proved to show there is a significant influence of communication (X2) variable to the dependent variable Job Spirit (Y)